THE ROLE OF TEACHERS AS ROLE MODELS IN ISLAMIC RELIGIOUS EDUCATION IN SENIOR HIGH SCHOOLS - Habib Akbar Nurhakim (Al-Masail: Journal of Islamic Studies, 2023)
This study aims to explore the role of Islamic Religious Education (PAI) teachers as role models in shaping students' character and morals in senior high schools (SMA). The research method used was a qualitative approach with a case study, involving in-depth interviews, participatory observation, and document analysis. The results showed that PAI teachers who demonstrate consistency between teachings and daily behaviors can improve students' discipline, ethics, and participation in learning. The interactive and contextual teaching methods applied by teachers also contribute significantly to students' understanding and application of religious values. The novelty of this research lies in its holistic approach, considering the influence of external environments such as social media and family in the formation of student character. The research provides global benefits by offering practical strategies to improve the quality of Islamic religious education and support the role of teachers as role models in various international contexts.